Spi-B Promotes the Recruitment of Tumor-Associated Macrophages via Enhancing CCL4 Expression in Lung Cancer - Huang, Qiumin; Liu, Junrong; Wu, Shuainan; Zhang, Xuexi; Xiao, Zengtuan; Liu, Zhe; Du, Wei (Frontiers in Oncology, 2021)
Tumor immune escape plays a critical role in malignant tumor progression and leads to the failure of anticancer immunotherapy. Spi-B, a lymphocyte lineage-specific Ets transcription factor, participates in mesenchymal invasion and favors metastasis in human lung cancer. However, the mechanism through which Spi-B regulates the tumor immune environment has not been elucidated. In this study, we demonstrated that Spi-B enhanced the infiltration of tumor-associated macrophages (TAMs) in the tumor microenvironment using subcutaneous mouse models and clinical samples of human lung cancer. Spi-B overexpression increased the expression of TAM polarization- and recruitment-related genes, including CCL4. Moreover, deleting CCL4 inhibited the ability of Spi-B promoting macrophage infiltration. These data suggest that Spi-B promotes the recruitment of TAMs to the tumor microenvironment via upregulating CCL4 expression, which contributes to the progression of lung cancer.